IMPLEMENTASI KEBIJAKAN PROGRAM KAMPUNG KELUARGA BERENCANA - KAMPUNG BAIMAN (KKB-KB) DI KOTA BANJARMASIN - normajatun normajatun; Sitna Hajar Malawat; Fika Fibriyanita (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2018)
Developing countries are always experiencing the main problem of development, where one of the points of development problems concerning the problem of a large population with a low quality of life Banjarmasin city government has a policy. namely Kampung Keluarga Berencana - Kampung Baiman (KKB-KB). The KKB-KB program not only prioritizes family planning programs but all sectors, such as health development, population administration and residential development. The KKB-KB program is expected to improve the quality of life of the community. This study uses a qualitative approach to collect data and analyze data then interpreted.